Analysis of Misbehaviors and Satisfaction With School in Secondary Education According to Student Gender and Teaching Competence - Granero-Gallegos, Antonio; Baños, Raúl; Baena-Extremera, Antonio; Martínez-Molina, Marina (Frontiers in Psychology, 2020)
Effective classroom management is a critical teaching skill and a key concern for educators. Disruptive behaviours disturb effective classroom management and can influence school satisfaction if the teacher does not have the competencies to control them. Two objectives were set in this work: to understand the differences that exist in school satisfaction, disruptive behaviours and teaching competencies according to the gender of the students; and to analyse school satisfaction and disruptive student behaviours based on perceived teaching competence. 758 students participated (male = 45.8%) from seven public secondary schools in the Murcia Region (Spain). The age range was between 13 and 18 years (M = 15.22; DT = 1.27). A questionnaire composed of the following scales was used: Competencies Evaluation Scale for Teachers in Physical Education, School Satisfaction and Disruptive Behaviours in Physical Education. Linear Multilevel Regression Models performed with the SPSS v.23 MIXED procedure was used for statistical analyses. The results revealed statistically significant differences based on gender and physical education teaching competencies. In conclusion, the study highlights that physical education teacher skills influence disruptive behaviours in the classroom, and that this is also related to school satisfaction. Furthermore, it highlights that boys showed higher levels of negative behaviours than girls.